HIGH LEVEL OF OCCULT HEPATITIS B VIRUS INFECTION IN TREATMENT-NAÏVE HIV INFECTED PATIENTS IN COTONOU, BENIN - AFFOLABI, DISSOU (My University, 2017)
Abstract- Human Immunodeficiency Virus (HIV) and Hepatitis B virus (HBV) infections share the same routes of transmission and are both endemic in sub-Saharan Africa. Proper management of these infections require reliable diagnosis of co-infected patients. We aimed to assess the magnitude of HBV infection in treatment-naïve HIV infected patients in Cotonou. This cross-sectional study was conducted from July 2014 to January 2015 on consecutively recruited treatment-naïve HIV infected patients attending the National Reference Center for Research and Management of HIV infection. Blood was collected from each patient for detecting HBs antigen (HBs Ag) by ELISA, HIV viral load, HBV viral load and CD4 counts. In total, 133 patients were included with a mean age of 38.3 years and a male to female ratio of 1.0:2.0. HBs Ag was positive in 15 (11.3%) of the patients while HBV viral load was detected in 52 (39.1%). The rate of occult hepatitis B (OBI) e.g. negative HBs Ag but positive HBV viral load was 27.8%. Patients with OBI were more likely to have low HBV viral load (p < 0.001) than those without OBI. In conclusion, the prevalence of OBI is high among treatment-naïve HIV infected patients in Cotonou. Universal access to molecular tests is needed in the country to detect HBV infection in these patients.
Keywords: HBV; HIV; Occult hepatitis; Benin.